Sportember Program As A Community Motivational Causa Doing Recreational - Dedi Kurnia; Sri Marini; Lu’luwatin Rosdiana Aprilia (STKIP Muhammadiyah Kuningan, 2023)
Sportember is a program of a tourist destination in The North Bandung Area that offers sports programs. The program is inseparable from the current public interest in sports and raises the motivation of the community to do recreational sports. The purpose of the research is to find out the cause of the community to do recreational sports through the Sportember program in The North Bandung area in 2021. This research uses a quantitative method through a survey approach. The population of this study is visitors to the tourist area of North Bandung, precisely Hotel and Resorts Sindang Reret Cikole. From this population, 100 respondents were sampled through a random sampling technique. Data collection was carried out through community motivation questionnaires. The result of the study is that the motivation of the community towards recreational sports through the Sportember program in The North Bandung area has a percentage of 77%, so it can be concluded that the motivation of the community towards recreational sports through the Sportember program in North Bandung area is high.